Formation of ICT competencies for future physics teachers - Shuyushbayeva, N.N.; Damekova, S.K.; Tanasheva, N.K.; Altayeva, G.S. (KU Publ., 2020)
The article discusses effective ways to use IT-services in teaching future physics teachers. This reflects the mutual understanding between the teacher and the student based on the use of modern information technologies in the development of the modern educational process. Some IT-services in teaching meet modern requirements. But this does not mean the chaotic use of any platform, programs, and software applications, that is, it is necessary to take into account the specifics of the subject, the pedagogical and psychological state of students. Based on this, the article describes what digital competencies should be used in the training of future physics teachers. Video lectures and audio lectures, infographics, visual lectures made in Mindmap, and Vyond on the discipline “Methodological basis of solving physical tasks” have a great influence on the comprehensive search of students. The article analyzes the necessity and relevance of using information technologies in the educational process but also discusses ways to implement them practically. This creates skills for students to use digital competencies to expand their knowledge. There are also ways to conduct questionnaires, tests, and reflections in various formats that allow students to test their knowledge. The types of tasks created in the effective applications used in the teaching of physics are given.
Болашақ физика мұғалімдерінің цифрлық құзыреттіліктерін қалыптастыру
Формирование цифровых компетенций будущих учителей физики
Keywords: IT-services; ICT competencies; methods of teaching physics; platforms; interactive learning; infographics; requirements; tasks